Developing English Speaking Teaching Materials Through Task-Based Learning for TheEighth-Grade Students Of MTs S Mutafawiq Aini - Sunarty, Rizqy; Asnawi (International Journal of Educational Research Excellence (IJERE), 2026)
The objectives of this study were to develop English-speaking materials through Task-Based Learning for eighth-grade students at MTs S Mutafawiq Aini, and to investigate the effectiveness of the developed materials in improving students' English speaking skills. This study employed a Research and Development method to design English speaking skills using a task-based learning approach. Educational R&D is a development model in which the findings of research are used to design new products and procedures that are systematically field-tested. Based on the research findings and discussions, several conclusions were drawn, and English-speaking materials were developed using the ADDIE model and validated by experts. The development process included the analysis of learners’ needs, design of task-based content, and implementation in real classroom settings. Expert validation showed that the developed materials were of high quality, with an average validity of 90.25%, and were categorized as 'Very Good.' The materials were relevant, engaging, and aligned with the Merdeka Curriculum. The field trial results revealed a significant improvement in the students’ speaking performance. The average score increased from 64.5 to 82.25, demonstrating that TBL effectively enhanced fluency, accuracy, and confidence. Students’ positive responses confirmed that the developed materials were interesting, enjoyable, and useful in motivating them to actively speak English. Overall, Task-Based Learning has proved to be an effective approach for developing English-speaking materials that promote communicative competence and learner autonomy.